UNDERSTANDING THE ROLE OF FOMO (FEAR OF MISSING OUT) IN IMPULSE PURCHASE FOR SMES - Rachman, Adryan; Efawati, Yen; Anmoel, Jason Timothy (Kesatuan Press, 2024)
This study examines the influence of price discounts on impulse buying through live streaming among e-commerce users in Indonesia. The research adopts a quantitative approach, utilizing a survey methodology with questionnaires distributed to a purposive sample of 152 consumers from the Dolee Branded Store. Data were analyzed using SmartPLS 4.0 software, employing the PLS-SEM analysis method. The findings reveal that price discounts significantly directly impact impulse buying behavior. Furthermore, price discounts also significantly affect live streaming, which, in turn, substantially influences impulse buying. The results indicate that live streaming acts as a mediating variable, enhancing the effect of price discounts on impulse purchases. This study underscores the importance of integrating price discount strategies with live streaming to drive impulse buying behavior in the e-commerce sector effectively. By leveraging live streaming as a promotional tool, businesses can maximize the impact of their discount offers, leading to increased consumer engagement and sales. These insights provide valuable implications for marketers and e-commerce platforms aiming to enhance their promotional effectiveness and customer acquisition strategies.